Operations strategy - Slack, Nigel; Lewis, Michael 1969- (Pearson Education Limited, 2024)
"Operations strategy is a major source of competitive advantage in for-profit businesses and the route to achieving social welfare in not-for-profit enterprises. No matter what sector, it can have a huge impact - not just in the short term, but also on an enduring basis. Just look at those companies that have transformed their prospects through the way they manage their operations resources strategically: Amazon, Apple, Disney, IKEA, Intel, Lego, Ocado, Ryanair, Samsung, Wipro, Zara and many more, all have developed their strategic operations capabilities to the point where they represent a formidable asset. (And all are among the many examples to be found in this text.) These firms have found that it is the way they manage their operations, and their resources in general, that sets them apart from, and above, their competitors"--